A radar study of growth and decay of thunderstorms around Bombay during the pre-monsoon season - MUKHERJEE, A. K.; KUMAR , S.; KRISHNAMURTHY, G. (MAUSAM, 1977)
Rates of growth and decay of ’Cb’ clouds as seen through 3 cm radar have been studied for Bombay and neighbourhood for April 1974. The rate of growth varied from 2 to 16 m.p.s. These were compared with those obtained from T-phi-gram analysis. The observed values were lower than the calculated ones. Assuming lower value of observed rate of growth to be due to entrainment of environmental air by rising parcel, the amount of entrainment has been calculated for a particular case. The rates of decay are found to vary from 0.5 to 7 m.p.s.